2016
DOI: 10.2139/ssrn.2884246
|View full text |Cite
|
Sign up to set email alerts
|

Banking Access for the Poor: Adoption and Strategies in Rural Areas of Bangladesh

Abstract: The progress of Mobile Banking (M-banking) is unsatisfactory in terms of achieving a key objective, i.e. to reach the inaccessible unbanked customers at an affordable cost for financial inclusion. We identify the causes to this problem through the investigating the factors affecting the adoption of m-banking in remote areas of Bangladesh using a 236 primary sample of m-bank customers from seven geographical locations and across professions. We document a positive effect of perceived ease of use, trusts, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Based on the respondents' perceptions greenwashing occurs in food, beverage, cosmetics, medicine, brickfield, tourism and transportation sectors very often. Rahman (2023d) reported that eco-tourism run by travel agencies, tour operators, hotels, motels and resorts is a quick and superficially "green" visit within a conventional package.…”
Section: Greenwashingmentioning
confidence: 99%
“…Based on the respondents' perceptions greenwashing occurs in food, beverage, cosmetics, medicine, brickfield, tourism and transportation sectors very often. Rahman (2023d) reported that eco-tourism run by travel agencies, tour operators, hotels, motels and resorts is a quick and superficially "green" visit within a conventional package.…”
Section: Greenwashingmentioning
confidence: 99%
“…using AI technologies and behavioural intention to use such techniques. Similarly, Shang and Wu's (2017) study on mobile shopping, Rahman and Hoque's (2018) study on telemedicine adoption, Dhiman et al ( 2019) study on smartphone fitness app adoption, Alam et al (2020) study on health services, Tam et al (2020), study on customer satisfaction have focused on studying behavioural intention to use the AI.These studies looked at technology use from various angles, and they made the case that factors of technology adoption intention can be used to better understand user psychology. The results, however, may be distinctly or barely different from study to study and from one context to another, so they are not consistent across all studies.…”
Section: Behavioural Intention To Usementioning
confidence: 99%
“…On the other hand, it was reported that environmental degradation and depletion of natural resources in Bangladesh occur faster than in the past decades due to poverty and pressures of overpopulation (Rahman 2023 a, b, c, d). Greenwashing occurs in food, beverage, cosmetics, medicine, brickfield, tourism and transportation sectors very often in the name of green (Rahman 2023e). Therefore, the study aims to identify the bottlenecks associated with the green economy in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%